Defining Biologically Meaningful Biomes Through Floristic, Functional, and Phylogenetic Data - Cardoso, Domingos; Moonlight, Peter W.; Ramos, Gustavo; Oatley, Graeme; Dudley, Christopher; Gagnon, Edeline; Queiroz, Luciano Paganucci de; Pennington, R. Toby; Särkinen, Tiina E. (Frontiers in Ecology and Evolution, 2021)
While we have largely improved our understanding on what biomes are and their utility in global change ecology, conservation planning, and evolutionary biology is clear, there is no consensus on how biomes should be delimited or mapped. Existing methods emphasize different aspects of biomes, with different strengths and limitations. We introduce a novel approach to biome delimitation and mapping, based upon combining individual regionalizations derived from floristic, functional, and phylogenetic data linked to environmentally-trained species distribution models. We define ‘core Biomes’ as areas where independent regionalizations agree and ‘transition zones’ as those whose biome identity is not corroborated by all analyses. We apply this approach to delimiting the neglected Caatinga seasonally dry tropical forest biome in northeast Brazil. We delimit the ‘core Caatinga’ as a smaller and more climatically limited area than previous definitions, and argue it represents a floristically, functionally, and phylogenetically coherent unit within the driest parts of northeast Brazil. ‘Caatinga transition zones’ represent a large and biologically important area, highlighting that ecological and evolutionary processes work across environmental gradients and that biomes are not categorical variables. We discuss the differences among individual regionalizations in an ecological and evolutionary context and the potential limitations and utility of individual and combined biome delimitations. Our integrated ecological and evolutionary definition of the Caatinga and associated transition zones are argued to best describe and map biologically meaningful biomes.